Techmentoring program: A school-based ICT initiative for teachers - Alda, Whisky Ricaza; Elejorde, Gregorio Cyrus; Alda, Rivika Coronado (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2022)
The emergence of computers and their associated technologies has prompted educators to examine and transform their classroom practices to respond to the call for technology integration. Although there have been several ICT training initiatives conducted for teachers, ICT tools are not yet seamlessly integrated into the classrooms. This study aimed to find out the effectiveness of the Techmentoring program as a school-based ICT initiative among non-ICT teachers in basic education. This study utilized a one-group pretest-posttest quantitative research design to determine teachers’ attitudes and skills before and after the Techmentoring program along different phases of ICT uses which are familiarization, utilization, integration, reorientation, and evolution. Survey questionnaires are used before and after the implementation of the program. Considering the principles of mentoring, only 23 teachers are selected to be part of the Techmentoring program. The findings of the study revealed a significant difference in teachers’ attitudes and skills before and after Techmentoring. Teachers’ perceived skills and attitudes in navigating the varied ICT tools have significantly improved, supported by their feedback on the implementation. It further revealed that mentor-supported professional development and not just merely training is an effective strategy in ensuring that teachers will acquire the skills needed for them to effectively integrate ICT tools in the teaching-learning process.